2018
DOI: 10.1002/jaal.908
|View full text |Cite
|
Sign up to set email alerts
|

Ninth‐Grade Students’ Use of Graphical Representations in Social Studies Writing

Abstract: Graphical representations are frequently used but normally not explicitly taught in social studies. The authors explore how to utilize the often unused potential of disciplinary graphical representations in student writing by offering insight into a Norwegian ninth‐grade classroom where students were scaffolded to use such representations. The authors scrutinized how these students invented connections between modes as they combined and transformed different representations in their texts. The authors found hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Thacker et al (2019) discussed how elementary social studies teachers might engage their students in studying and creating infographics. Others have proposed infographic or graphical representation lessons in middle and high school as a way to present research or writing (Staurseth & Haland, 2019; Yearta et al, 2018). We build on the existing scholarship to offer infographic instruction, mentor texts, and examples that could be used by elementary and middle‐grade teachers.…”
Section: How To Make It Work: a Framework Of Infographic Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…Thacker et al (2019) discussed how elementary social studies teachers might engage their students in studying and creating infographics. Others have proposed infographic or graphical representation lessons in middle and high school as a way to present research or writing (Staurseth & Haland, 2019; Yearta et al, 2018). We build on the existing scholarship to offer infographic instruction, mentor texts, and examples that could be used by elementary and middle‐grade teachers.…”
Section: How To Make It Work: a Framework Of Infographic Learningmentioning
confidence: 99%
“…Lamb et al (2014) observed that “a strong infographic depicts multiple layers of related information and data, often densely, displaying deep interrelationships among variables and ideas” (p. 27). Teachers and students can examine how these multiple layers work together to convey meaning and critically deconstruct model infographics (Lamb et al, 2014; Staurseth & Haland, 2019; Yearta et al, 2018). Table 1 includes the guiding questions that may be used when analyzing infographics.…”
Section: How To Make It Work: a Framework Of Infographic Learningmentioning
confidence: 99%
See 2 more Smart Citations